Przymioty i zadania żony według Jana Chryzostoma - Krynicka, Tatiana (Vox Patrum, 2009)
Like many others Church fathers John Chrysostom considers virginity preferable to marriage. At the same time, being an interpreter of Saint Paul’s doctrine, he repeats that marriage is a splendid God’s mystery (Ephesians 5, 31-33). That is why he explains to the Christian men what kind of women they have to marry in order to become happy husbands, as well as draws Christian wives’ attention to their duties. According to Chrysostom, a man who seeks a wife should follow example of the servant, sent by Abraham back to his homeland to get a bride for his son, Isaac. First of all, he must aim to find a righteous woman. Bride’s wealth, as well as physical beauty are able to make her husband happy only provided that she lives faithfully serving God. Saint John teaches that God expects married Christian women to submit to their husbands, to live a chaste life, to take care of household while the man is about his public business, to be modest in their appearance and manners. Many times he sharply points out women’s vices and faults. On the other hand he holds in high esteem their virtues and sensibility, as well as demands that husbands should love their wives, treat them with respect, be loyal to them. Analyzing female characters pictured by John Chrysostom, we often come across the types well-known through ancient Greek poetry.